ASSESSING THE MACROECONOMIC ANOMALIES IN MAGELANG CITY - Nur Afiyah Maizunati (Riset Ekonomi Pembangunan, 2020)
The economic dynamics in Magelang City, although quite impressive in the last five years, but have had anomalies in several years. The interrelated achievement of several macro indicators does not show synergy with various existing economic theories. This study examines the economic anomaly that occurred in Magelang City through the analysis of the relationship of several macro indicators with OLS regression and the Vector Autoregressive (VAR) model. The research results show that there is a negative relationship between the inflation variable and the unemployment rate on GDP. It was also found that GDP had significant granger causality over unemployment rate. Unemployment rate showed a negative response since the first period due to changes in the inflation rate. But in the 5th to the 10th years its fluctuations began to shrink. Meanwhile the GDP responded negatively to the dynamics of inflation with fluctuations that widened throughout the year. The determination of the cut-off point for inflation figures needs to be carefully formulated so that all related indicators can move dynamically but harmoniously.